Experimental investigations on electrorheological properties of lubricating oils containing ionic liquid. Part 2. Testing in dielectric spectroscopy - Jarosław Juda; Tomasz Jan Kałdoński; Tadeusz Kałdoński; Mateusz Mrukiewicz (Biuletyn Wojskowej Akademii Technicznej, 2020)
The paper presents the results of investigations of two mixtures and their ingredients i.e. base insulating oils and ionic liquids as electrically active additives using, so called, dielectric spectroscopy. In part 1 of the study [1], the ER effect was found in both mixtures when they were subjected to an external constant electric field with the intensity of E ≤ 0.2 kV·mm–1. However, the electrorheological effect was short-lived and unique on the same liquid sample, which suggested significant changes in its internal structure. Using the HP 4192 A Hewlett Packard impedance analyzer, the variability of their dielectric constans (), as well as the resistance (R) and the conductivity (σ), as a function of the frequency (f) of the constant electric field BIAS-u (DC) was assessed for different values of the applied voltage (U). Repeated tests were also carried out on the same samples of mixtures to observe how the originally applied BIAS field affects the further behavior of the liquid in the electric field. Based on the results of the research, the basis for confirming the symptoms of changes in the internal structure of mixtures, resulting, from the action of an external electric field, leading to the disappearance of the ER effect was obtained. In order to recognize the mechanism of disappearance of the ER effect, in situ microscopic tests of the prepared mixtures, subjected to an external electric field, will be carried out. Keywords: electrorheological effect, lubricating oils, ionic liquids, dielectric spectroscopy